PENGARUH TRANSFER PRICING AGGRESSIVENESS, LEVERAGE, DAN FIRM SIZE TERHADAP TAX AVOIDANCE - Rita Dewi, Ni Made; Noviari, Naniek (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.08.TAHUN.2024DO - 10.24843/EEB.2024.v13.i08.p07, 2024)
Tax avoidance is a strategy to legally minimize tax payments by exploiting the weaknesses of tax provisions. The purpose of the study is to empirically prove the effect of transfer pricing aggressiveness, leverage, and firm size on tax avoidance. All mining companies listed on the Indonesia Stock Exchange for the 2017-2021 period were selected as the population in this study. Determination of the sample using a non-probability sampling approach with purposive sampling technique. There were 12 companies selected as the research sample, so that 60 units of observation were obtained. Data analysis technique using panel data regression analysis. The results of the analysis show that transfer pricing aggressiveness has no effect on tax avoidance, leverage has no effect on tax avoidance, and firm size has a negative effect on tax avoidance in coal mining companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This shows that an increase in transfer pricing aggressiveness and leverage in a company does not always indicate an increase in tax avoidance, and the larger the size of a company, the lower the level of tax avoidance in the company.